2013
DOI: 10.1227/neu.0b013e31828ba793
|View full text |Cite
|
Sign up to set email alerts
|

Hemangioblastomas and Neurogenic Polyglobulia

Abstract: Neurogenic polyglobulia occurs in a subset of patients with hemangioblastomas. This phenomenon is mostly observed in VHL mutation carriers, but also occurs in patients with sporadic hemangioblastomas. Removal of the tumor results in the permanent cure of polyglobulia. Our observations suggest that polyglobulia is an effect by the tumor itself, either due to paraneoplasia or extramedullary hematopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…There is no increase in hematocrit in HOXB7-Cre driven Vhlh knockouts (data not shown). This pattern of focal erythropoiesis resembles the pattern observed in VHL patients, who develop polycythemia only rarely, despite tumor-associated extramedullary erythropoiesis [ 34 ].…”
Section: Discussionsupporting
confidence: 55%
“…There is no increase in hematocrit in HOXB7-Cre driven Vhlh knockouts (data not shown). This pattern of focal erythropoiesis resembles the pattern observed in VHL patients, who develop polycythemia only rarely, despite tumor-associated extramedullary erythropoiesis [ 34 ].…”
Section: Discussionsupporting
confidence: 55%
“…In this study we found a significant association of polyglobulia and tumor size. Interestingly, the literature of the distant past stated incidences for polyglobulia much higher than in more recent studies [ 2 ]. In 1972, Palmer [ 11 ] published a case series of 81 patients with hemangioblastomas stating that 25 patients (49%) of the patients with available Hb levels (51 cases) suffered from polyglobulia.…”
Section: Discussionmentioning
confidence: 91%
“…Hemangioblastomas are highly vascular neoplasms, which can occur as sporadic tumors or as part of the von Hippel–Lindau (VHL) disease [ 1 ]. They comprise approximately 3% of all tumors of the central nervous system and are mainly located in the cerebellum and spinal cord [ 2 ]. The tumors are composed of a dense reactive angiogenetic capillary network with “stromal” cells in between, which are the neoplastic component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIF-2α has been demonstrated to be a transcriptional target of STAT5, and STAT5 activation can drive glucose uptake and metabolic supply in hematopoietic cells 16 . The upregulation of the STAT5 target GLUT1 also suggests STAT5-activation mediating selective HIF cascade activation.…”
Section: Resultsmentioning
confidence: 99%